The views of school leaders regarding gaining universal values in socio-cultural trips - Öztürk, Semattin; Akcil, Umut (Frontiers in Psychology, 2022)
In the globalizing world, it is seen that life is more intertwined with different cultures. Therefore, intercultural sensitivity has vital importance for a peaceful harmonious common life. In order to ensure this sensitivity, societies must unite with common accepted values. In this regard, the adoption of universal values expressed by the UNESCO-UNICEF has particular importance. Therefore, schools have important responsibilities. Schools may prefer out-of-class activities in the development of positive sensitivity behaviors. In this study, the sensitivities developed by secondary-school students, who are the target group, towards living universal values after participating in out-of-school socio-cultural short-term trip activities were examined. The research adopts the phenomenological approach, which is one of the qualitative research methods. Interview techniques were used in accordance with this model. In line with the purpose of this research, the school administrators, who have the ability to witness the changes in the behavior of the children during and after the socio-cultural planned trip activities and who can best interpret them by filtering, have been reached. According to this criterion, 51 school administrators were selected. The results of the research revealed that short-term socio-cultural trips abroad have effects on living-universal values. It was observed that the positive behaviors in the school environment continued after the trip. We can say that, the development of sensitivity towards living-universal values also positively affects students' intercultural sensitivity. As a result, it is recommended that school administrators give importance to such activities.